2008
DOI: 10.1007/s11999-008-0292-6
|View full text |Cite
|
Sign up to set email alerts
|

Femoral Shortening During Hip Arthroplasty Through a Modified Lateral Approach

Abstract: We describe a modification of the direct lateral approach to the hip that provides excellent femoral and acetabular exposure and an easy way to shorten the proximal femur and equalize leg length. The approach also is useful for lower extremity elongation while preserving muscle continuity and minimizing postoperative complications. The exact amount of shortening can be calculated and planned preoperatively and measured and corrected intraoperatively if necessary. It avoids the necessity for osteotomies of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 17 publications
0
13
1
Order By: Relevance
“…First, disuse atrophy of the abductor is always seen in a high dislocated hip; second, the abductor insertion may be compromised when performing osteotomy and joint reduction with powerful distal traction; finally, the femoral stem is further impacted distally into the canal by the use of shortneck after lesser trochanteric osteotomy, which always reduces the hip offset [21]. Therefore, risk of abductor weakness is generally higher for lesser trochanteric osteotomy than for the subtrochanteric type which had complete retention of abductor and use of standard neck prosthesis [22].…”
Section: Discussionmentioning
confidence: 99%
“…First, disuse atrophy of the abductor is always seen in a high dislocated hip; second, the abductor insertion may be compromised when performing osteotomy and joint reduction with powerful distal traction; finally, the femoral stem is further impacted distally into the canal by the use of shortneck after lesser trochanteric osteotomy, which always reduces the hip offset [21]. Therefore, risk of abductor weakness is generally higher for lesser trochanteric osteotomy than for the subtrochanteric type which had complete retention of abductor and use of standard neck prosthesis [22].…”
Section: Discussionmentioning
confidence: 99%
“…proximal femoral shortening osteotomy with distal advancement of the greater trochanter, splitting the femoral shaft with proximal shortening, a modified lateral approach combined with chisel detachment of the anterior and posterior halves of the continuous tendon of the gluteus medius and vastus lateralis muscle and a step-cut shortening osteotomy with or without angular correction [1,2,7,8,13,18,20]. We used the step-cut osteotomy to secure the fragments against rotation and to obtain correction of antetorsion and angulation combined with shortening if a Schanz osteotomy had been previously performed.…”
Section: Discussionmentioning
confidence: 99%
“…These anatomical changes differ according to the formation of the disease as well as the operations the patient has undergone [2,5]. In case of subluxation; acetabulum is shallowed, wide and elliptic; while anteromedial wall of acetabulum is insufficient, there is a good bone stock in the posterior wall.…”
Section: Introductionmentioning
confidence: 99%
“…Significant femoral changes are short femoral neck, small femoral head, increased femoral neck angle and anteversion, posterior transposition of great trochanter and femoral medullar narrowing in isthmus region [8]. To regain hip function, the center of hip rotation should be transferred medially, and abductor forces should be transferred laterally [2,5,[9][10][11]. It has been reported that when placing the acetabular cup, an uncovered space of up to 30-40% is acceptable [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation